Neutralization of membrane complement regulators improves complement-dependent effector functions of therapeutic anticancer antibodies targeting leukemic cells - Mamidi, Srinivas; Höne, Simon; Teufel, Claudia; Sellner, Leopold; Zenz, Thorsten; Kirschfink, Michael (OncoImmunology, 2015)
Complement-dependent cytotoxicity (CDC) is one of the effector mechanisms mediated by therapeutic anticancer monoclonal antibodies (mAbs). However, the efficacy of antibodies is limited by the resistance of malignant cells to complement attack, primarily due to the over-expression of one or more membrane complement regulatory proteins (mCRPs) CD46, CD55, and CD59. CD20-positive Burkitt lymphoma Raji cells and primary CLL cells are resistant to rituximab (RTX)-induced CDC whereas ofatumumab (OFA) proved to be more efficient in cell killing. Primary CLL cells but not CD52-positive acute lymphoblastic leukemia (ALL) REH cells were sensitive to alemtuzumab (ALM)-induced CDC. Upon combined inhibition on Raji and CLL cells by mCRPs-specific siRNAs or neutralizing antibodies, CDC induced by RTX and by OFA was augmented. Similarly, CDC of REH cells was enhanced after mCRPs were inhibited upon treatment with ALM. All mAbs induced C3 opsonization, which was significantly augmented upon blocking mCRPs. C3 opsonization led to enhanced cell-mediated cytotoxicity of leukemia cells exposed to PBLs or macrophages. Furthermore, opsonized CLL cells were efficiently phagocytized by macrophages. Our results provide conclusive evidence that inhibition of mCRPs expression sensitizes leukemic cells to complement attack thereby enhancing the therapeutic effect of mAbs targeting leukemic cells.